2005
DOI: 10.1073/pnas.0409217102
|View full text |Cite
|
Sign up to set email alerts
|

Receptor editing in peripheral B cell tolerance

Abstract: Receptor editing or secondary Ig gene rearrangement occurs in immature, autoreactive B cells to maintain self-tolerance. Here we show that nonspontaneously autoimmune mice immunized with a peptide mimetope of DNA develop peptide-and DNA-reactive antibodies. Antigen-specific B cells display a follicular B cell phenotype. As these cells move into the memory compartment, many express RAG protein and acquire expression of both and light chains. Thus, this study provides evidence for receptor editing occurring in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 42 publications
6
60
0
Order By: Relevance
“…Using a tetrameric form of this peptide, we are able to detect the tetramer-reactive (Tet + ) compartment, which is enriched in DNA-reactive B cells (16,17). In a previous study, we reported that RAG expression is detected in a subpopulation of the splenic antigen-reactive compartment within a short time window following immunization with DWEYS-MAP (17). In this study, we sought to further delineate the developmental stage of antigen-reactive RAG-expressing cells and to understand the mechanism and function of receptor editing in an ongoing response.…”
Section: Rag Is Induced In Postactivation Early Memory/preplasma B Cementioning
confidence: 99%
See 1 more Smart Citation
“…Using a tetrameric form of this peptide, we are able to detect the tetramer-reactive (Tet + ) compartment, which is enriched in DNA-reactive B cells (16,17). In a previous study, we reported that RAG expression is detected in a subpopulation of the splenic antigen-reactive compartment within a short time window following immunization with DWEYS-MAP (17). In this study, we sought to further delineate the developmental stage of antigen-reactive RAG-expressing cells and to understand the mechanism and function of receptor editing in an ongoing response.…”
Section: Rag Is Induced In Postactivation Early Memory/preplasma B Cementioning
confidence: 99%
“…When it is part of a decapeptide octamerized on a polylysine backbone (DWEYS-MAP), it can induce a SLE-like serology in the nonautoimmune BALB/c mouse strain, while immunization with the polylysine backbone (MAP-core) alone does not (15). Because we are able to identify the antigen-specific B cells in the spleens of mice immunized with DWEYS-MAP using a fluorochrometagged tetrameric peptide (16), we were able to demonstrate RAG expression and l light chain expression in antigen-activated autoreactive B cells (17). Importantly, we failed to detect RAG expression in antigen-specific B cells in the response to a control peptide mimetope of phosphorylcholine that does not generate autoreactivity, despite provoking a robust anti-phosphorylcholine response.…”
Section: Introductionmentioning
confidence: 99%
“…However, and in contrast with this previous report, more than a half of included ͞ B cells showed a mature follicular phenotype (CD23 high ͞CD21 int ) and demonstrated that such cells are not necessarily trapped in the MZ. It has also been hypothesized that dual BCR expression resulted from receptor editing of an autoreactive primary Ig HC͞LC combination (22,23,25,26). In such models of LC inclusion, the expression of multiple antigen receptors was thought to dilute the autoreactive BCR and permit autoreactive cells to escape deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor editing also occurs in normal mice during the selection of immature B cells and may be a major pathway of tolerance induction by rescuing cells with autoreactive BCR from deletion (or anergy) provided that they express a new receptor (20,21). Nevertheless, this editing process intrinsically bears the risk of generating B cell clones that will migrate toward peripheral lymphoid organs while carrying dual or multiple antigen receptors, one of those potentially being autoreactive (22)(23)(24)(25)(26). Moreover, autoreactivity may not be the only way to promote receptor editing because some non-autoreactive knockin mice also showed extensive secondary rearrangements, likely due to a low expression of the knockin gene (27,28).…”
mentioning
confidence: 99%
“…Subsequent experiments with GFP-Tg mice showed that RAG expression in spleens was restricted to immature transitional B cells [52,53]. However, recent studies on mice with spontaneous [54] or induced [55] autoimmunity have reported on RAG expression and receptor editing in the mature peripheral B cell population. Although we have not yet investigated individual peripheral B cell populations, our experiments clearly indicate that anti-DNA-autoreactive B cells express RAG-2 in peripheral B cells and have ongoing secondary L chain rearrangements in the periphery (as demonstrated by LM-PCR), which result in BCR editing.…”
mentioning
confidence: 99%